Expressão do canal Kv10.1 em pacientes com câncer colorretal: implicações diagnósticas e terapêuticas - Silva, Yasmim Vieira (2024)
Colorectal cancer is one of the most common types of cancer globally, with 45,630 new cases and 20,245 deaths in Brazil in 2023, attributed to factors such as exposure to carcinogens and population aging. Despite its high incidence, it can be effectively treated if detected early, although current diagnostic methods have limitations. Voltagegated potassium channels (Kv) play a crucial role in cell cycle regulation and tumor progression. Kv10.1, in turn, is a potassium channel restricted to some types of tissue under healthy conditions, such as neuronal tissue, but its presence has been documented in peripheral tissues in patients diagnosed with colorectal cancer, breast cancer, cervical cancer, and others. Thus, the aim of this study was to evaluate the gene expression profile for Kv10.1 in tumor and healthy samples from patients with colorectal cancer, as well as in cell lines, correlating these results with clinicopathological data, and evaluating in silico and in vitro cell viability the susceptibility of the channel as a treatment target. Twenty-seven fresh tissue samples were obtained from tumor and healthy tissue of patients diagnosed with CRC (> 18 years old) at Napoleão Laureano Hospital (HNL). The project was approved by the Research Ethics Committee under the registration CAAE: 5.017.299. The tumor cell lines used were HT-29, LoVo, HCT-116, K562, and HEK-293. Gene expression analysis (mRNA) of Kv10.1 was performed using real-time PCR technique, using the GAPDH normalization gene and SYBR Green dye. Our data showed that there was higher expression of Kv10.1 in tumor samples compared to adjacent healthy tissue from the same patient (p=0.0282) by MannWhitney Test. Kv10.1 gene expression was found to be correlated with age, being more expressed in patients under 60 years old (p=0.0112), with location, being more expressed in tumors located on the left side (p=0.0173), with tumor size, being more expressed in tumors smaller than 5cm (p=0.0343), and with early stage (I/II) (p=0.0078). The Kv10.1 channel underwent molecular docking study using compounds A398 and 5-Fluorouracil (5-FU) as ligands. The compounds demonstrated negative binding energy values, with A398 (-9.59 Kcal/mol) showing better interaction with Kv10.1 compared to 5-FU (-4.05 Kcal/mol), a drug used clinically for CRC treatment. In the MTT assay, compound A398 significantly inhibited the viability of HCT-116 cells, with IC50 of 18.24µM at 24h and 9.87µM at 72h. On the other hand, 5-FU showed significant inhibition only after 72h, with IC50 of 14.85µM, indicating time and concentration dependence for its efficacy. Therefore, it is possible to observe good potential for using Kv10.1 as a biomarker for CRC diagnosis, while the approach for its use as a therapeutic target should be better investigated.